Konotasi Warna Pada Masyarakat Bali - I Gede Dodi Raditya Putra (Program Magister Linguistik Universitas Udayana, 2017)
The purpose of this paper is to identify the connotation of colors in Balinese that commonly occur in society such as: black, white, yellow, green, red, orange and purple. The research approach in this paper is a qualitative research. The data used in this paper were collected through information given by Balinese native speakers dealing with the use of colors in connotation meaning and the use of special treatment for naming colors. Data was analyzed by X-phemysm by Allan (2001) to find the meaning of connotation of colors. The result showed that red is associated with dysphemism, white has been found with dysphemism, euphemism and orthophemism. The connotation of green is dysphemism and euphemism. Yellow is associated with euphemism. Color naming in Balinese, orange or nasak gedang is associated with euphemisme and purple or pelung is associated with dysphemisme. Color naming in Balinese happened because of their life experience.